Effects of remuneration on financial performance: The case of Ghana water company limited in the ho municipality - Kpordzo Moses (knust, 2025)
A thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of MASTER OF SCIENCE IN ACCOUNTING AND FINANCE